COVID-19 Trend Estimation in the Elderly Italian Region of Sardinia - Puci, Mariangela Valentina; Loi, Federica; Ferraro, Ottavia Eleonora; Cappai, Stefano; Rolesu, Sandro; Montomoli, Cristina (Frontiers in Public Health, 2020)
From the last December 2019 a novel coronavirus (COVID-19) quickly globally spreads from China. Currently, the COVID-19, defined as the new pandemic as declared by the World Health Organization (WHO), reached over 750.000 confirmed cases worldwide. The virus spread in Italy from the 22nd February, and the number of related cases arenumber of related cases is currentlystill increasing assuming important proportions. Furthermore, given that numerous a relevant proportion of infectedious people need hospitalization in Intensive Care Unit, this may be a crucial issue for National Healthcare System’s capacity. WHO underlines the importance of specific disease regional estimationestimate, aimed to put in place proportioned and adequate control measures and identifying to guarantee adequate funding to increase ICU beds and for the production of personal protective equipment. Our aim is to investigate the current COVID-19 epidemiological context in Sardinia region (Italy) and to estimate the transmission parameters using stochastic model to establish the number of infected, recovered and died people expected. Based on available data from official Italian and regional sources, we described distribution of infected cases in Sardinia induring the period between 2nd to 15th March, 2020. To better reflect the actual spread of COVID-19 in Sardinia based on data at 15th March (first Sardinian declared outbreak), two Susceptible-Infectious-Recovered-Dead (SIRD) models have been developed, describing the best and the worst scenarios. We believe that our findings represent a valid contributione to a better understandding the epidemiological context of COVID-19 in Sardinia. Our analysis can help health authorities and policymakers to address the right interventions to deal with the rapidly expanding health emergency.